Handbook of Pediatric Retinal Disease - Wright, Kenneth W.; Spiegel, Peter H.; Thompson, Lisa (Springer New York : Imprint: Springer, 2006)
Based on Dr. Wright's classic major reference, Handbook of Pediatric Retinal Disease outlines the latest findings in diagnosing retinal disorders in children's and the best available treatment options. Distilling the essentials of these somewhat uncommon discorders and diseases into a portable, complete and authorative pocket reference, this handbook offers a complete picture of how to best treat pediatric patients. Specifically, the introductory chapters on the specifics of pediatric ophthalmology (embryology, post-natal development and the pediatric exam) will help newcomers to pediatric practice fully grasp the subtle differences in pediatric care. The chapters are written by leading experts in the field and are presented in a user-friendly format, relying on heavily illustrated in color plates, clincally helpful tables, charts, and decision-making guidelines. This approach will enable the practitioner (whether specialist or generalist) to make the most accurate diagnosis and choose the most effective treatment option.